Making success tangible: reengaging female opportunity youth in Baltimore, MD. (July 2020) - Offiong, Asari; Lewis, Quiana; Powell, Terrinieka W
Opportunity Youth represents over four million young people who are not in school and are unemployed. In Maryland, Baltimore City has the highest rate of youth disconnection. In spite of this, there are limited culturally relevant program models specific to the experiences of urban, African American youth. None focus on the unique needs of young women who are disconnected from school and work. In partnership with two local youth organizations, a 6-week program was co-developed and implemented to address the social and emotional needs of female opportunity youth in Baltimore. The program promoted self-efficacy, fostered a supportive network of trusted adults and increased awareness of resources. Lessons learned included the importance of program flexibility, the value of youth voice in program development, and the need to reframe how success is measured. This case study highlights a novel approach to bolstering the development of female opportunity youth.